Prince of fire [compact disc, unabridged] - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2004)
Now Allon is back in Venice, when a terrible explosion in Rome leads to a disturbing personal revelation: the existence of a dossier in the hands of terrorists that strips away his secrets, lays bare his history. Hastily recalled home to Israel, drawn once more into the heart of a service he had once forsaken, Gabriel Allon finds himself stalking an elusive master terrorist across a landscape drenched in generations of blood, along a trail that keeps turning in upon itself, until, finally, he can no longer be certain who is stalking whom. And when at last the inevitable showdown comes, it's not Gabriel alone who is threatened with destruction-for it is not his history alone that has been laid bare.